Membangun Kepemimpinan melalui Pelatihan Dasar di Kalangan Remaja Gereja HKBP Ressort Laguboti, Kabupaten Toba - Ginola Carloz Hutabarat; Amelia Nainggolan; Indah Simbolon; Agustinus Purba; Ruslan Juliana Pardosi (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to form church youth leadership through basic training carried out in a participatory and educational manner at the HKBP Church, Laguboti Resort, Toba Regency. The activity was carried out on May 2, 2025 at the Simanarium Sipaholon and was attended by 50 active church youth. The implementation methods used include lectures, interactive discussions, leadership simulations, group dynamics, and direct mentoring. This activity is designed in several stages, namely preparation, implementation, and evaluation. The results of the activity showed that the training had a positive impact on participants' understanding of leadership that is devoted and has a Christian character. Participants experienced changes in attitude, increased participation, and showed a new spirit in service. This training has proven to be able to form reflective and responsible leadership characters, as well as encourage active involvement of youth in church life.